PENGEMBANGAN ASSESMENT FOR LEARNING BERBASIS HIGHER ORDER THINGKING SKILLS (HOTS) MELALUI PENDEKATAN LESSON STUDY TERHADAP IMPLEMENTASI KURIKULUM 13 PADA PEMBELAJARAN MATEMATIKA DI MAN 1 PADANGSIDIMPUAN - Almira Amir (Jurnal Dedikasi Pendidikan, 2020)
This research is motivated by the implementation of the 2013 curriculum as a whole not being implemented because the facilities and infrastructure are still inadequate, the teacher has not yet maximally carried out the learning assessment because the assessment method has not been shown to be comprehensive observations due to the large number of students, and the test questions have not yet arrived at HOTS achievements. The subjects used to test the practicality and effectiveness of the assessment for learning tools were 32 students in class X-1. This type of research is used in 4-D R&D models (Define, Design, Development & Disseminate). Data collection techniques were carried out using the check list method, focus discussion group (FGD), peer assessment sheets, self-assessment sheets, and description form tests.The results showed that, the validation results from experts on the HOTS-based assessment for learning developed were feasible to use with the results 1) the results of the RPP validation of 0.76; 2) the results of the validation of peer assessment sheets 0.906; 3) the results of the validation of the self-assessment sheet 0.875; 4) the results of the validation test sheet form description for the content of 0.824 and for languages of 0.903. Practicality test results show practical use, namely 1) the results of student answers to peer assessment sheets obtained an average value of 81.12 and the results of answers to the self-assessment sheet obtained an average value of 79.90, the results are included in the good category, 2) Results the answers to the test obtained an average value of 82.62, median value of 84.38, mode value of 93.75, and a standard deviation of 11.36. The highest value obtained was 96.88 and the lowest value obtained was 43.75. Based on the acquisition category the test score is a good category.